2017
DOI: 10.1097/md.0000000000007591
|View full text |Cite
|
Sign up to set email alerts
|

Myopathy in hyperthyroidism as a consequence of rapid reduction of thyroid hormone

Abstract: Rationale:Myalgia and elevated creatine kinase (CK) are occasionally observed during the treatment of hyperthyroid patients. Relative hypothyroidism resulted from rapid thyroid hormone reduction had been promoted as a plausible cause of these myopathic changes, however rarely reported.Patient concerns:We hereby presented a 20-year-old female with Grave's disease, who developed myopathy and elevated CK during rapid correction of thyroid hormone.Diagnoses:Relative hypothyroidism-induced myopathy.Interventions:An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Hypothyroid myopathy manifests in the setting of hypothyroidism and entails muscle rigidity, cramps and general weakness, pronounced in the extremities [2,56]. Both have also been tied to rhabdomyolysis, especially hypothyroidism, with elevated serum CK enzymes [55], while a similar entity has been described in aggressively-treated hyperthyroidism [57].…”
Section: Endocrine-related Myopathiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypothyroid myopathy manifests in the setting of hypothyroidism and entails muscle rigidity, cramps and general weakness, pronounced in the extremities [2,56]. Both have also been tied to rhabdomyolysis, especially hypothyroidism, with elevated serum CK enzymes [55], while a similar entity has been described in aggressively-treated hyperthyroidism [57].…”
Section: Endocrine-related Myopathiesmentioning
confidence: 99%
“…In greater detail, a 2015 study on a pediatric population with thyroid disorders showed that impaired overall cognitive function may be tied to hypothyroidism myopathy, with deficits in attention, memory, arithmetic and verbal skills being mainly reported [57]. Mental retardation has also long been associated with severe hypothyroidism and is one of the main reasons as to why neonatal screening is being considered as a standard clinical practice, while the differential diagnosis of acquired cognitive deficits in older individuals typically includes thyroid function tests [58].…”
Section: Endocrine-related Myopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous cases have reported statin-induced hypothyroid myopathy4; myopathy due to relative hypothyroidism resulting from rapid thyroid hormone reduction in a hyperthyroid patient5; and myopathy that resolved with thyroxine administration; however, this patient was clinically euthyroid on presentation and did not have proximal weakness on examination6; a hypothyroid patient with associated myopathy but with a TSH level far lower (50) than the patient in this case report 7. In our case, there was neither statin use nor any other precipitants.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies reported that some Graves’ disease patients with oral antithyroid drugs (ATDs) manifested myalgia and increased serum CK levels [ 4 , 5 , 6 , 7 ]. Many patients reported taking ATDs, which were presumed to be the cause of muscular lesions [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%